STRUCTURAL DEIGN OF KEY COMPONENTS OF FEEDER BASED ON TOPOLOGY OPTIMIZATION AND MULTI-OBJECTIVE OPTIMIZATION - TANG HuaPing; LI HongXing; JIANG YongZheng; LIU Jie (Jixie qiangdu)
In view of the problem that the feeder often fails due to insufficient strength,the transient dynamics of a certain type of vibrating feeder under typical working conditions is analyzed based on the finite element method（FEM）. At the same time,the dynamic stress measurement under the corresponding working conditions is carried out. The results show that the main reason for the failure of the feeder is the unreasonable design of the spring upper seat structure. Therefore,based on the variable density method and substructure technique,a topology optimization model of constrained stress and volume fraction is established with the combined strain energy of spring upper seat as the optimization objective function,based on sensitivity analysis and least square method,a response surface model of first order torsion,bending frequency and total mass is established. At last,genetic algorithm is used to carry out the multiple object optimization to the response surface model,and the optimal solution set of Pareto is obtained. The results show that the natural frequencies of the optimized structures are increased by 4. 17% and 6. 30%,respectively. The maximum dynamic stress is reduced by 46. 4% and the overall stiffness and structural reliability of the feeder are improved.